Pengaruh Variasi Temperatur Hardening dan Tempering Paduan AlMgSi-Fe12% Hasil Pengecoran terhadap Kekerasan - Sumpena Sumpena; Wardoyo Wardoyo (Jurnal Engine: Energi, Manufaktur, dan Material, 2018)
The purpose of this research is to know the effect of Heat Treatment Hardening-Tempering Alloy AlMgSi–Fe12% foundry result to hardness and toughness. The test was carried out on raw material and material test specimen after obtaining Hardening heat treatment at 600℃ and quenching with SAE 20 oil medium. While Tempering variation at temperature 200℃, temperature 250℃ and temperature 300℃ with detention time for 15 min at each temperature, each heat treatment. Hardness testing method is done by standard micro Vickers test method with 100 gf loading. The result of raw material testing for hardness value is 60,92 VHN. Test results after heat treatment process at temperature 200℃ cause hardness value increased by 63,50 VHN. At temperature 250℃ cause hardness value decreased to 59,94 VHN. At temperature 300℃ cause hardness value increase to 76,98 VHN